2019
DOI: 10.5812/jjm.68389
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota, Lactic Acid and Short Chain Fatty Levels of Infants Following Rotavirus Infection Revealed by Illumina Miseq High-Throughput Sequencing and HPLC Method

Abstract: Background: Rotavirus (RV) is one of the major causes of acute gastroenteritis in infants. It is indispensable to demonstrate the relationship between the diversity and richness of gut microbiota and RV infection using more accurate and effective technology. Objectives: To investigate the differences in fecal microbiota, lactic acid, and short-chain fatty acids (SCFAs) levels between rotaviralinduced diarrhea (RD) infants and healthy (H) infants. Methods: The infants comprised of 25 infants aged few days to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
5
1
Order By: Relevance
“…The results of our study have confirmed the previous data and proved that dysbiotic changes in the intestine develop in all patients in the early stages of RVI, which is expressed in a decrease in absolute concentrations of all saccharolytic microflora metabolites: C2-C4 and a significant decrease in AI. Our results are confirmed by modern literature data about low Shannon's and Simpson's indices in young children with RVI, which characterize the species diversity of the intestinal microbiota [16]. The degree of the intestinal microflora metabolic and structural disorders is correlated with an increase in the amount of undigested sugars in the faeces, which, according to the literature [4,5], is the pathogenetic basis for the osmotic diarrhea development in RVI.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of our study have confirmed the previous data and proved that dysbiotic changes in the intestine develop in all patients in the early stages of RVI, which is expressed in a decrease in absolute concentrations of all saccharolytic microflora metabolites: C2-C4 and a significant decrease in AI. Our results are confirmed by modern literature data about low Shannon's and Simpson's indices in young children with RVI, which characterize the species diversity of the intestinal microbiota [16]. The degree of the intestinal microflora metabolic and structural disorders is correlated with an increase in the amount of undigested sugars in the faeces, which, according to the literature [4,5], is the pathogenetic basis for the osmotic diarrhea development in RVI.…”
Section: Discussionsupporting
confidence: 87%
“…However, significant differences in the results of SCFA detection have been identified by some researchers. Thus, L. LI, D. Huang showed a lowering of only the level of lactic acid (Bifidobacterium and Lactobacillus meta bolites) in infants with RVI in the absence of changes in total pool of SCFA and C2-C4 concentrations [16]. Other researchers emphasized a significant decrease in the total amount of volatile acids and absolute concentrations of each of them (C2-C5) in the acute period of RVI [7,17], demonstrating a sharp decrease in anaerobic metabolism of oligosaccharides as a result of impaired intestinal microbiocinosis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Some researchers suggested that the lower levels of butyrate and propionate in; feces of CD and ulcerative colitis (UC) diarrhea patients should be the consequence of an inflammation-driven intestinal dysbiosis (11). Further, De et al found the depletion of butyric acid in feces of was the dominant SCFA (35), while, in current study, only butyric acid was detected in the feces of RD and H infants who were between 4 and 9 months old. In addition, there was no significant difference in the levels of these five SC-FAs in the feces between 0-6-month-old infants with and without RD (35), on the contrary, the level of butyric acid in RD infants was significantly reduced compared to H infants in this study.…”
Section: Discussioncontrasting
confidence: 44%